Bixas-Pretas experiences in Geography: between images of control and tactics of self-definition (PerCursos, 2025)
I wrote this manuscript with the aim of arguing and proposing creative approaches to thinking about issues of gender and sexuality in geographical science, in particular black masculinities based on the experiences and identities referred to here as Bixas-Pretas. Conceptually, I will base this research on geographers' interpretations of gender, sexuality, and masculinity, as well as on the images of control described by Patricia Collins. Regarding methodological procedures, this text was created based on a bibliographic survey, autobiographical records, and discourse analysis. Finally, I am in favour of the use of images of control in research rooted in Feminist and Sexuality Geographies as potential concepts and interpretative keys to germinate and strengthen studies on dissident racialised masculinities. From the discovery: Bixas-Pretas as revolutionary bodies and affections.
Keywords: body-space; race; masculinity; sexuality; write living